May allergy and cancer be etiologically related? - Rouzbahani, Goodarz; Darougar, Sepideh; Mansouri, Mahboubeh; Mousavi, Farideh (Researcher Bulletin of Medical Sciences, 2025)
Objective: Due to increased worldwide prevalence of cancers, efforts have been made to identify the correlations between chronic disorders as probable risk factors in inducing cancers. Allergies have been long proposed as having promoted or protecting roles against oncogenesis. This study aimed to investigate the probable role of allergic disorders in cancer development in children. Materials and Methods: Children between 2 to 18 years of age with a history of malignancy referred to Shohadaye Tajrish Hospital (Tehran, Iran), from 2011 to 2015 were recruited to this study. They were all referred to Allergy Clinic for further evaluation for the presence of allergic disorders or any histories of it. A questionnaire was filled for every patient including demographic information such as their age, sex, type of cancer, signs and symptoms of allergy and their severity at onset and before the diagnosis of cancer. Results: The study was conducted with a total of 56 patients with a mean age of 10.8±4.5 years (2-18 years) and a diagnosis of cancer. The most common cancers in this study were osteosarcoma (39.3%) and acute lymphocytic leukemia (19.6%). Twenty-four (43%) children had a history of allergic disease before the diagnosis of cancer. The most common allergic disease was allergic rhinitis (21.4%). Eosinophilia was detected in 44.6% of children. Conclusion: To conclude, in children suffering from cancers, particularly those with solid tumors, allergic disorders and eosinophilia were significantly prevalent and also the relative risk of cancers in food allergies were rather high.